Analysis of Customer Loyalty: An Empirical Study of The Product IM3 Indosat on FEUKI Student - Hutasoit, SE., MSi., MSE, Posma Sariguna Johnson Kennedy; Simanjuntak, Priskila Theodora; Tobing, Fenny BNL (Fundamental Management Journal, 2016)
This study aims to determine the level of loyalty of FEUKI students to use Indosat IM3 products, and to know the attributes/factors that lead to these customers loyalty to IM3 products. Source of data used is derived from primary data obtained from questionnaires distributed to eighty-eight of the respondents who have used at least a year IM3 Indosat continuously. The methods used are using the qualitative analysis techniques Fishbein and Likert scale. The conclusion can be drawn from the fishbien analysis, where the results showed that the students' attitude FEUKI as customer responses to a product that is worth 243.24 Indosat IM3 in the category quite satisfied, with a percentage of 77.44%. students have shown loyalty to Indosat IM3 products. The level of loyalty are the majority (90.1%) high loyalty. Attributes that affect customer loyalty are in quadrant II in the Cartesian diagram. The indicators referral is an attribute/dominant factor affecting the loyal attitude of the students.Keywords : customer loyalty, products, fishbien analysis